PENGARUH GAME ONLINE DAN POLA TIDUR DI SMARTPHONE TERHADAP KUALITAS TIDUR REMAJA USIA 12 s/d 19 TAHUN DI RT.05 RW 02 DESA PANGKALAN KAB. PANDEGLANG - Yuliawati, Ayies; Depeda, Andre; Sari, Rina Puspita (Nusantara Hasana Berdikari, 2022)
Online games can be played on smartphones that are connected to a network of many teenagers who continue to play until their sleep patterns fall apart. Sleep quality is a sleep condition experienced by individuals to create freshness and health when awake. Playing online games until late at night and sleeping patterns are not on time can affect the quality of sleep in adolescents. The purpose of the study was to determine The Influence of Online Games and Sleep Patterns on Smartphones on the Quality of Sleep for Teenagers Age 12 to 19 Years in RT.05 RW 02 Pangkalan Village, Kab. Pandeglang. Quantitative method with a cross sectional approach, the population in this study were teenagers in the village of Pangkalan Kab. Pandeglang as many as 20 respondents. Sample collection technique with total sampling. The instrument used is a questionnaire sheet. The results of the study used univariate analysis, and Bivariate analysis using chi square test. Also multivariate using multiple linear regression test found the influence of online games and sleep patterns on smartphones on adolescent sleep quality, as evidenced by the results of the significance of 0.000 where <0.05 which means there is an effect.